Middle-range clustering of nucleotides in genomes - Mrázek, J; Kypr, J (Computer applications in the biosciences, 1995)
We propose a novel, transparent and very simple algorithm to analyze middle-range correlations in genomic nucleotide sequences. Analysis by this algorithm of the EMBL Nucleotide Sequence Database demonstrates that all four nucleotides cluster in the genomic nucleotide sequences of eukaryotes on the scale of several hundred base pairs. In prokaryotes, the clustering is weak but still evident. The non-dominant three bases are deficient in the clusters, while A is the most deficient nucleotide in the clusters of C, and vice versa, and G is the most deficient nucleotide in the clusters of T, and vice versa. The algorithm also detects CG islands, extending over 1 kb, in vertebrate sequences. In plants, the CG islands are shown to be much smaller, if they exist at all. A clustering tendency is also exhibited by the TA doublet. Other doublets do not cluster. We observe no strong correlation between nucleotides separated in genomes by > 1 kb.
Keywords: algoritmy; molekulární sekvence - údaje; DNA; genom; Animals; Humans; sekvence nukleotidů; Base Sequence; Genome; lidé; Algorithms; Nucleotides; zvířata; nukleotidy; Molecular Sequence Data